Preparing Unsocialized Youths for Additional Professions in Craft Fields - Ishmurodova G.I (Zien Journals, 2022)
In this article, the content of entrepreneurial activities is shown in the orientation of school graduates, unorganized youth to national craft professions, non-organized youth, craft activities, the main directions of folk crafts, carpentry and entrepreneurial professions, cradle preparation and furniture production and sale
Keywords: profession; craft; entrepreneurship; woodworking